Developing a national indicator of intravenous antibiotic use to support timely review of antibiotics in Scottish hospitals. Issue 2 (28th February 2020) - Malcolm, William; Baxter, Linsey; McNicol, Megan; Sneddon, Jacqueline
Abstract : Background: To address increasing antibiotic use in acute hospitals, the Scottish Antimicrobial Prescribing Group developed a quality improvement (QI) initiative to support reliable review of patients started on intravenous (IV) antibiotics within 72 hours. This will reduce unnecessary continuation of antibiotics, ensure personalised treatment and appropriate IV to oral switch with associated benefits for patients of reduced risk of device related infections and potential for earlier discharge from hospital. Methods Using data obtained from the Hospital Medicines Utilisation Database, a national database of secondary care medicines use in Scotland, we examined trends in IV antibiotic use between 2013 and 2017. We then projected the current trend forward to 2021 to inform development of national indicator to optimise IV antibiotic use. Results: In 2017, IV antibiotics accounted for 32.9% of all antibiotic use in Scottish hospitals. Annual IV antibiotic use (defined daily doses per 1000 population per day) increased by 20.5% between 2013 and 2017. We estimated a further projected increase of 12.5% between 2018 and 2021. To measure the impact of our QI initiative SAPG agreed to employ a national indicator with a target that 'use of IV antibiotics in hospitals will be no higher in 2021 than it was in 2018'. Conclusion: This national indicator will evaluate progress with achieving reliable and timely review of IV antibiotic therapy to reduce hospital antibiotic use and contribute to reduction in total antibiotic use in humans which is a key ambition of the UK AMR National Action Plan.